2022
DOI: 10.1038/s41550-022-01841-6
|View full text |Cite
|
Sign up to set email alerts
|

A dehydrated space-weathered skin cloaking the hydrated interior of Ryugu

Abstract: Without a protective atmosphere, space-exposed surfaces of airless Solar System bodies gradually experience an alteration in composition, structure and optical properties through a collective process called space weathering. The return of samples from near-Earth asteroid (162173) Ryugu by Hayabusa2 provides the first opportunity for laboratory study of space-weathering signatures on the most abundant type of inner solar system body: a C-type asteroid, composed of materials largely unchanged since the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 68 publications
0
18
2
Order By: Relevance
“…More recent studies have identified additional opaque components in lunar samples including Fe silicides (e.g., Hapkeite and associated phases; Anand et al 2004) and phases that likely form through oxidation processes by reaction with surrounding glass and/or H 2 O, including FeO and Fe 3 O 4 (e.g., Thompson et al 2016;Burgess & Stroud 2018). In returned samples from S-type and C-type asteroids, we observe nanoparticles enriched in S, including FeS, MgS (Noguchi et al 2011(Noguchi et al , 2014(Noguchi et al , 2023, and FeNiS. When we consider the composition of opaque phases beyond the Moon, the microstructural characteristics produced via space weathering are predicted to be heavily dependent on the starting composition of the surface.…”
Section: Predicted Microstructural and Chemical Products Of Space Wea...mentioning
confidence: 61%
“…More recent studies have identified additional opaque components in lunar samples including Fe silicides (e.g., Hapkeite and associated phases; Anand et al 2004) and phases that likely form through oxidation processes by reaction with surrounding glass and/or H 2 O, including FeO and Fe 3 O 4 (e.g., Thompson et al 2016;Burgess & Stroud 2018). In returned samples from S-type and C-type asteroids, we observe nanoparticles enriched in S, including FeS, MgS (Noguchi et al 2011(Noguchi et al , 2014(Noguchi et al , 2023, and FeNiS. When we consider the composition of opaque phases beyond the Moon, the microstructural characteristics produced via space weathering are predicted to be heavily dependent on the starting composition of the surface.…”
Section: Predicted Microstructural and Chemical Products Of Space Wea...mentioning
confidence: 61%
“…It is similar to that of Ivuna-like carbonaceous chondrites (Ito et al 2022;Nakamura et al 2023;Yada et al 2022;Yokoyama et al 2023;Leroux et al 2023), which are the most primitive chondrites and have a composition almost identical to that of the bulk solar system (Lodders 2003). Noguchi et al (2022Noguchi et al ( , 2023 and Matsumoto et al (2024) have observed unique features not previously observed in meteorites, including particular surface textures attributed to space weathering. They consist in a submicrometer sized assemblage of glassy silicates containing vesicles and nanosulfides that are draping the surface of typical phyllosilicaterich Ryugu grains.…”
Section: Introductionmentioning
confidence: 80%
“…The section mounted on the TEM grid was thinned to a thickness of ∼150 nm using 16 or 30 kV Ga + ion beams. The damaged layers were removed using a 2 kV Ga + ion beam (Noguchi et al 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Recent high-resolution TEM analysis reported that some surfaces of Ryugu particles have space weathering features caused by solar wind irradiation and/or (micro-)meteorite bombardment 49 . Amongst them, the outermost frothy layer is interpreted as the melting products of the phyllosilicates-rich matrix by the latter process on Ryugu's surface.…”
Section: Discussionmentioning
confidence: 99%